QCA-based Implementation of Budget-friendly and Energy-Efficient Exclusive-OR/Exclusive-NOR Gates - Gyanesh Savita; Namit Gupta (International Journal of Electro-Mechanics and Material Behaviour, 2023)
Quantum-dot cellular automata (QCA) is a novel nanoscale computational approach that proposes reduced dimensions, lower power consumption, increased speed, and deliberate design as a solution to the scaling challenge associated with CMOS technique. QCA is a nascent nanotechnology that utilizes the Coulomb repulsion principle. Quantum computing has emerged as a highly effective paradigm for the creation of energy-efficient hardware at the nanoscale. This article presents implementation of a very efficient and simplified 2-bit QCA XOR gate in QCA Designer tool. The suggested design exhibits a reduced quantity of quantum cells and spatial dimensions compared to its most optimal pre-existing QCA configurations. The simulation results demonstrate that the proposed architecture exhibits superior performance compared to the most optimal existing layouts in terms of quantum cell count, area, latency, and quantum cost
Keywords: CMOS; Exclusive-NOR; Exclusive-OR; Majority Voter Gate; QCA